IPAD Implementation In Teaching English at SMP Islam Al-Azhar Cairo Banda Aceh - Miftahul Jannah; Zahratul Fitri; Nurjannah Nurjannah (Journal of English Teaching and Linguistics, 2023)
Despite the fact that incorporating technology into English learning at school has numerous benefits, there are currently very few teachers who have done so. The iPad has been widely used as a learning medium in English language study in various nations. However, using an iPad for English language learning in Banda Aceh is still unusual. Descriptive qualitative research with a case study approach was carried to describe how the teacher uses the iPad in teaching English for the seventh-grade students at SMP Islam Al Azhar Cairo Banda Aceh. An observation sheet and interview guide were used to gather the data. The data analysis was processed in the form of condensation data, display data, and conclusion data which are proposed by Miles, Huberman, and Saldana (2014). The findings show that some applications were used by the English teacher to support the learning atmosphere, such as; iTunes U App, Keynote App, Pages App, and iTunes U App. Furthermore, the web browsing function is the most commonly used and important feature for students at SMP Islam Al-Azhar Cairo Banda Aceh. It provides quick and easy access to the students and the support it provides for collaboration.